The Hyden Fault Scarp, Western Australia: Paleoseismic Evidence for Repeated Quaternary Displacement in an Intracratonic Setting - Clark, D.; Dentith, M.; Wyrwoll, K.; Yanchou, L.; Dent, V.; Featherstone, Will (Taylor & Francis Ltd, 2008)
We present new paleoseismicity data for the 30 km long and 2.5 m high Hyden fault scarp in Western Australia, which, when combined with the results of previous research, provides the most extensive record of surface-rupturing earthquakes yet assembled for an 'active' Australian intracratonic fault. The data indicate that four to five surface-rupturing earthquakes have occurred on the Hyden Fault during the Quaternary (E1, ca 20 ka; E2, ca 55 - 50 ka; E3, ca 100 - 90 ka; and two events E4 and E5, 4200 ka). Activity is episodic, with single seismic cycle slip rates varying from 0.03 mm/y to 50.01 mm/y. Paleoearthquake magnitudes are estimated to have been in the order of Mw 6.8. The identification of a similar fault scarp immediately north west of the Hyden scarp, and of two air photo lineaments to the west of the Hyden scarp, indicates that strain is distributed among a family of faults in this region. The presence of multiple nearby active faults suggests that the recurrence of severe ground shaking in the Hyden region is more frequent than indicated by the paleoseismic data presented here.